The use of film documentary in social science research: audio-visual accounts of the 'migration crisis' from the Italian island of Lampedusa. Issue 1 (1st January 2021) - Franceschelli, Michela; Galipò, Adele
Abstract : The importance of visual evidence – and particularly films and videos – has become more prominent with the fast pace of technological development that has made filming more easily accessible. Since the early 20th century, films have been used as a data collection method in social science research, but less attention has been given to their potential for research dissemination. It is well documented that visual representations are powerful means to broadcast public discourses. The Arab Spring in 2011 and the increasing movement of people across the Mediterranean Sea are a case in point. Images and videos of people trying to reach Europe have contributed to the construction of what is often referred to as the 'Mediterranean migration crisis'. In this article, we explore the process of making a film documentary about the people in the Italian island of Lampedusa, a key transitory site for migrants, and how they deal with the challenges of this 'crisis' while trying to respond to the local struggles of their isolated community. Drawing on the analysis of 'audio-visual accounts' – as the filmed verbal elaborations that broadcast themes emerging from social science research – we reflect on the potential and drawbacks of film documentaries for both knowledge production and research dissemination.